DETERMINAN KEPUTUSAN PENDANAAN PADA PERUSAHAAN PUBLIK DI INDONESIA (Pengujian Pecking Order Theory dan Trade Off Theory) - Ni Putu Ayu Darmayanti; Ni Putu Santi Suryantini (Universitas Islam Sultan Agung (UNISSULA), Faculty of Economics, Department of Accounting, 2017)
Policy regarding capital structure involves a tradeoff between risk rate of return which the increase in debt can causean increased risk of the company, but on the other hand also increased the level of return expected by shareholders.Less than optimal debt management can even lead to bankruptcy of the company. Previous studies conducted inthe Indonesian capital market find different results related to the effect of several variables that affect corporatefinancing decisions. The results of empirical research to prove the existence of the application of the pecking ordertheory (POT) and trade off theory (TOT) to firms in Indonesia. This study was conducted to examine again whethervariable dividend policy (proxied by the dividend payout ratio), profitability (proxied by return on assets), assetstructure (proxied by the composition of fixed assets), and the variability of the rate of profit (proxied by variablityof EBIT) significantly against the funding decision (diprosikan to debt ratio) at public companies in Indonesia 2012-2014. From the results of multiple linear regression analysis of the data 36 samples studied company, the conclusionthat the dividend policy and the structure of assets and a significant positive effect on financing decisions of publiccompanies in Indonesia 2012-2014. Profitability and variability of EBIT to the funding decisions in this study foundto be negative but not significant.Keywords : debt ratio, pecking order theory, trade off theory